Do Thyroid Ultrasonographic Features Change According to Age in Euthyroid Dogs? - Mueller, T. R. [UNESP]; Assis, M. M. Q. [UNESP]; Doiche, D. P. [UNESP]; Souza, L. P. [UNESP]; Pizzigatti, D. [UNESP]; Mamprim, Maria Jaqueline [UNESP] (Wiley-Blackwell, 2014)
The thyroid gland was assessed by ultrasound in healthy euthyroid mixed-breed medium size dogs in different age groups. The objective was to verify ultrasonographic imaging patterns in these groups, as well as to identify possible changes in imaging features resulting from ageing. Thirty dogs - 10 young (<1 year), 10 adult and 10 elderly - without clinical signs or history of thyroid gland disease with complete blood count and thyroid function tests within the reference values were evaluated. Each thyroid lobe was examined by ultrasound for shape, size, echogenicity and echotexture. The analysis of echogenicity and echotexture was made by histogram. Thyroid volume was estimated by the equation for ellipsoid (length x width x height) pi/6. The thyroid volume of the young dogs in this study had a tendency to be higher than in adult dogs (P = 0.068) and older dogs (P = 0.120). The height of the thyroid lobe in the longitudinal plane was significantly higher (P = 0.026) in young dogs compared with the other dogs. The echotexture and echogenicity had no significant differences between groups, but the echogenicity was greater in older dogs. The results point out that ultrasound imaging of the thyroid volume is influenced by age in euthyroid dogs.